Kontribusi Serapan Karbondioksida Tegakan Balangeran (Shorea balangeran (Korth.) Burck) dan Meranti Tembaga (Shorea leprosula Miq.) dalam Aksi Mitigasi Perubahan Iklim: Contribution of Carbon Dioxide Uptake The Stands of Balangeran (Shorea Balangeran (Korth.) Burck) and Copper Meranti (Shorea Leprosula Miq.) in Actions Climate Change Mitigation - Junaedi, Ajun; Saragih, Harry Martua; Yosep, Yosep; Indrayanti, Lies; Yulianti, Reri; Rizal, Moh (Jurusan Kehutanan, Fakultas Pertanian Universitas Palangka Raya, 2025)
This study aims to identify the distribution pattern of stem diameter and estimate the potential of biomass storage, carbon and CO2 uptake above ground of Balangeran (Shorea balangeran (Korth.) Burck) stands aged ± 5 years in the People's Seedling Garden and Copper Meranti (Shorea leprosula Miq.) aged ± 7 years in the Green Campus Seedling Garden of Palangka Raya University. The calculation method of estimating biomass and carbon storage and CO2 uptake of Balangeran and Copper Meranti stands in a non destructive manner using the Jaya et. al (2007), Heriansyah et. al (2009), SNI 7724 (2019) and IPCC (2006) allometric equations. The results showed that the distribution pattern of the diameter class distribution of Balangeran and Copper Meranti stands resembled a bell/ginger-shaped curve. The stem diameter class of Balangeran stands is dominated by 5-7 cm and Copper Meranti 8-10 cm. Balangeran stands have potential biomass storage of 70,715 tons/ha, carbon of 33,236 tonsC/ha and CO2 uptake of 121,976 tonsCO2/ha. While Copper Meranti stands have potential biomass storage of 29,307 tons/ha, carbon of 13,774 tonsC/ha and CO2 uptake of 50,552 tonsCO2/ha. Balangeran and Coper Meranti stands have a strategic contribution to climate change mitigation actions.